Effects Of Salmonella Pullorum Infection on Vaccinal Immunity Against Newcastle and Avian Influenza Diseases in Broiler Chickens (Texas Journal of Agriculture and Biological Sciences, 2022)
A study aimed to evaluate the effect of Salmonella Pullorum infection on vaccinal immunity against ND and AIV in a broiler. Before starting the study collected several samples from suspected infected flocks with S. Pullorum (OM988162.1), and identified by several biochemical test then molecular test PCR and confirmed isolates by sequencing. then take two hundred and fifty (Ross 308) Five groups of broiler chicks were formed. Each group has 50 chicks., as follow first group: infected with S. Pullorum and vaccinated against (NDV, AIV). Second group: infected with S. Pullorum and treated by (ciprofloxacin 10% 1ml / liter or 20 % 0,5 L for 7day and colistin 200million IU/0.5L for 7 days) also vaccinated against (NDV, AIV). Third group: infected with S. Pullorum and treated by (ciprofloxacin 10% 1ml/ liter or 20 % 0,5 L for 7day and colistin 200million IU/0.5L for 7 days) only. Fourth group: infected with S. Pollorum only as consider control positive. Five group: uninfected and unvaccinated as consider control negative. Antibodies titre (IgG and IFN-γ) against ND and AIV were significantly increased in G1 with the least histopathological changes in liver, kidney, bursa of fabricius, and thymus. G1 and G4 growth performance was significantly lower than that of treatment groups G2 and G3. Conclusion: S. Pullorum infection increased vaccinal immunity (IgG and IFN-γ) against Newcastle and influenza. Ciprofloxacin and colistin treatment improved body weight and weight gain